Self-rated health and smoking among physicians and general population with higher education in Estonia: results from cross-sectional studies in 2002 and 2014 - Kersti Pärna; Inge Ringmets; Sävelin Siida (BMC, 2019)
Abstract Background Poor self-rated health (SRH) and smoking have consistently been shown to be related to mortality. The aim of this study was to explore SRH and smoking among physicians and general population with higher education in Estonia in 2002 and 2014 and to analyse the association of SRH with smoking and sociodemographic factors. Methods This study was based on cross-sectional postal surveys among physicians and general population with higher education in Estonia n in 2002 and 2014. Calculation of age-standardized prevalence of SRH and current smoking with 95% confidence intervals (CI) was performed. Multivariate logistic regression analysis was used to measure association between SRH (at-least-good vs less-than good) and smoking status, study year, age group, ethnicity, and marital status. Fully adjusted odds ratios (OR) with 95% CI were computed. Results Age-standardized prevalence of at-least-good SRH was 71.3 and 80.6% among male physicians, 68.4 and 83.1% among female physicians, 45.4 and 67.4% among men with higher education, and 44.7 and 63.1% among women with higher education in 2002 and 2014, respectively. Age-standardized prevalence of current smoking was 26.0 and 15.6% among male physicians, 10.2 and 5.9% among female physicians, 38.7 and 22.2% among men with higher education, and 20.9 and 16.4% among women with higher education in 2002 and 2014, respectively. There was no significant gender difference in at-least-good SRH, but prevalence of current smoking was significantly higher among men in both study groups in 2002 and 2014. Compared to year 2002, odds to have at-least-good SRH was higher in 2014 (OR = 1.64; 95% CI 1.16-2.31 among male and OR = 2.36; 95% CI 2.02-2.75 among female physicians, OR = 1.49; 95% CI 1.07-2.07 among men and OR = 2.40; 95% CI 1.84-3.13). Odds to have at-least-good SRH was significantly higher among non-smokers (except female physicians), in the youngest age group, and among Estonians. Conclusions This study gave an overview of differences in SRH and smoking between two target groups with higher education in two timepoints highlighting the importance of addressing smoking cessation counselling and health promotion campaigns in the population by different subgroups in Estonia.